Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Sure, let's proceed step-by-step to solve the given equation using the provided information and approach.
Step 1: Understand the given equation and substitution
The original equation is:
[tex]\[ -2x + y = -12 \][/tex]
We are given that [tex]\( y = -2 \)[/tex]. We need to substitute [tex]\( y = -2 \)[/tex] back into the equation.
Step 2: Substitute [tex]\( y = -2 \)[/tex] into the equation
Substitute [tex]\( y = -2 \)[/tex]:
[tex]\[ -2x + (-2) = -12 \][/tex]
Step 3: Simplify the equation
Simplify the equation by substituting the value of [tex]\( y \)[/tex]:
[tex]\[ -2x - 2 = -12 \][/tex]
Step 4: Summary based on substitution
We then rewrite the given part of the equation as:
[tex]\[ -2x - 2 = -12 \][/tex]
So, replacing the term for [tex]\( y \)[/tex] in the original equation, we get:
[tex]\[ -2x + \boxed{-2} = -12 \][/tex]
Now, as requested, the equation after substituting [tex]\( y = -2 \)[/tex] back is:
[tex]\[ -2x + \boxed{-2} = -12 \][/tex]
This completes the substitution process for this problem.
Step 1: Understand the given equation and substitution
The original equation is:
[tex]\[ -2x + y = -12 \][/tex]
We are given that [tex]\( y = -2 \)[/tex]. We need to substitute [tex]\( y = -2 \)[/tex] back into the equation.
Step 2: Substitute [tex]\( y = -2 \)[/tex] into the equation
Substitute [tex]\( y = -2 \)[/tex]:
[tex]\[ -2x + (-2) = -12 \][/tex]
Step 3: Simplify the equation
Simplify the equation by substituting the value of [tex]\( y \)[/tex]:
[tex]\[ -2x - 2 = -12 \][/tex]
Step 4: Summary based on substitution
We then rewrite the given part of the equation as:
[tex]\[ -2x - 2 = -12 \][/tex]
So, replacing the term for [tex]\( y \)[/tex] in the original equation, we get:
[tex]\[ -2x + \boxed{-2} = -12 \][/tex]
Now, as requested, the equation after substituting [tex]\( y = -2 \)[/tex] back is:
[tex]\[ -2x + \boxed{-2} = -12 \][/tex]
This completes the substitution process for this problem.
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.